The Effect of Multimedia Learning to Raise the Awareness of Natural Vegetation Diversity Conservation in Maeka Community, Phayao Province : The Plant Genetic Conservation Project under the Royal Initiation of Her Royal Highness Princess Maha Chakri Sirindhorn - Somyaron, Wilawan (Journal of Roi Et Rajabhat University, 2020)
This research had the purposes as following: 1) to develop multimedia learning on natural vegetation diversity conservation in Maeka community, 2) to publish multimedia learning to the schools in the community and study the students’ satisfaction, and 3) to evaluate the awareness of natural vegetation diversity conservation. The target group was 73 students who were studying in grade 1-6at Baan HuaiKhian School Phayao province. The instruments used for this study were multimedia learning, an evaluation form on the appropriateness of the multimedia learning, an evaluation form on the awareness of natural vegetation diversity conservation, and an assessment form for students’ satisfaction towards the multimedia learning. The data were analyzed by using frequency, mean, standard deviation and t-test (dependent samples). The results revealed that: 1) There were 6 main aspects of the multimedia learning on natural vegetation in Maeka community which were 1) general knowledge about Rong Kham Luang forest park 2) deciduous dipterocarp forest 3) mixed deciduous forest 4) dry evergreen forest 5) others forest types, and 6) natural vegetation. The evaluation on the appropriateness of the multimedia learning was at a high level. 2) Students’ satisfaction towards multimedia learning was at a high level. 3) The mean scores of students on awareness of natural vegetation diversity conservation showed that after learning was higher than before learning with statistically significant difference at .01 level.